Preparation of Magnetic Composite Polyaniline/Fe3O4−Hydrotalcite and Performance in Removal of Methyl Orange - Thi Tuong An Tran; Huynh Thanh Linh Duong; Thi Thuy Phuong Pham; Tri Nguyen; Thi Dung Nguyen; Boi An Tran (Adsorption Science & Technology)
Magnetic composite fabricated from polyaniline and Fe3O4-hydrotalcite (Pan/MHT) was successfully applicated for removal of methyl orange (MO) from wastewater. The structure and properties of Pan/MHT were characterized by Fourier-transform infrared spectroscopy, scanning electron microscopy, X-ray diffraction, vibrating sample magnetometer, and Brunauer-Emmett-Teller adsorption isotherm. Adsorption kinetic results indicated that the adsorption process followed pseudosecond-order kinetic model (R2=0.999), MO adsorption onto Pan/MHT was well described by Freundlich isotherm (R2=0.994), and the MO adsorption capacity of 2 Pan/MHT obtained the highest with Qe=156.25 mg/g. Batch adsorption experiments were carried out using magnetic composite with the effects of initial MO concentration, solution pH, and adsorbent dosage. The results revealed that the magnetic Pan/MHT exhibited efficient adsorption of MO in the aqueous solution as a result of the affinity for organic dyes, microporous structure, and suitable surface area for adsorption (15,460 m2/g). The superparamagnetic behavior of Pan/MHT (withHc=18.56 Oe, Ms=23.38×10−3 emu/g, andMr=0.91×10−3 emu/g) helps that it could be separated from the solution and performs as an economical and alternative adsorbent to removal and degrade azo dye from wastewater. Pan/MHT was also investigated to reuse after desorption of MO in 0.1 M HCl, and the results show that 2 Pan/MHT can be reused for 4 cycles with Qe=79.66 mg/g.